Purchasing power, fruits vegetables consumption, nutrition status among elementary school student - Yohan Fallo; Adi Magna Patriadi Nuhriwangsa; Diffah Hanim (Intelektual Pustaka Media Utama, 2019)
Food purchasing power is usually defined as a household's economic ability to obtain food which is determined by measuring the income allocated for food purchase, the price of food consumed, and the number of family members. More than 50% of the sub-districts in South Central Timor are vulnerable to food consumption due to their low purchasing power, thus causing low fruits and vegetables consumption. To analyze the correlation between purchasing power, fruits and vegetables consumption, with nutrition status of elementary school students. Analytic observational using a cross sectional design. Sample size of 108 students was achieved using simple random sampling method. Independent variables are purchasing power, fruits and vegetables consumption. Dependent variable is nutrition status. Fruits and vegetables consumption data was collected using food frequency, purchasing power data was collected using questionnaires, and nutrition status was collected by calculating IMT/U. The statistics tests used were chi square test. The mean number of fruits and vegetables consumption of the elementary students was 0,36±0,483 and the mean number of purchasing power was 2,80±0,405. Bivariate study test results show a significant correlation between purchasing power and nutrition status (p=0,039) and a significant correlation between fruits and vegetables consumption and nutrition status (p=0,000). There is a correlation between purchasing power, fruits and vegetables consumption, and nutrition status in elementary school students.